Improving Student Science Literacy Skills Through the Use of Teaching Materials with Socioscientific Contexts on Newton's Gravity Material - Saefullah, Asep; Rostikawati, Diana Ayu (Universitas Muhammadiyah Makassar, 2024)
This research was motivated by the frequent appearance of news about social issues, such as tidal floods caused by eclipses, which are linked to Newton's theory of gravity. A teaching material was developed that integrated the issue of tidal flooding with physics concepts. The study aimed to determine how scientific literacy among students is influenced by using teaching materials in the context of socioscientific issues. The research methodology was quasi-experimental, utilizing a pretest-posttest design with one group. The study was conducted in the Physics Education Department at Sultan Ageng Tirtayasa University in Serang, Indonesia. The research sample consisted of fifty